The Role of Narcissism on Problematic Social Media Use in Emerging Adulthood Instagram Users - Usman, Dela Meiriza; Syihab, Aisyah; Dharma, Andri Setia (RSF Conference Series: Business, Management and Social Sciences, 2024)
The increasing use of social media, particularly among emerging adults, has brought attention to the issue of problematic social media use (PSMU). PSMU is characterized by excessive engagement and dependency. Previous studies have suggested a relationship between narcissism and problematic social media behavior. However, limited research has explored this relationship in the Indonesian context. This study aims to determine the role of each dimension of narcissism in problematic social media use by Instagram users emerging adulthood. The participants of this study were active Instagram users aged 18 to 25 years. This research was conducted using a quantitative approach. This study used convenience sampling and obtained 224 participants. The measuring instruments used in this study were the Narcissistic Admiration and Rivalry Questionnaire (NARQ) to measure narcissism variables in each dimension and the Bergen Social Media Addiction Scale (BSMAS) to measure problematic social media use variables. The analysis was conducted using multiple linear regression. The results of this study indicate that narcissism in the dimensions of admiration and rivalry dimensions (p<0.05) plays a significant and positive role in problematic social media use by emerging adulthood individuals who use Instagram. These findings suggest that individuals with higher levels of narcissistic traits, especially those seeking admiration or engaging in rivalry behaviors, are more likely to exhibit problematic social media behaviors.